Tumor diversity and the trade-off between universal cancer tasks - Jean Hausser; Pablo Szekely; Noam Bar; Anat Zimmer; Hila Sheftel; Carlos Caldas; Uri Alon (Nature Communications, 2019)
The evolutionary trade-offs faced by tumors are poorly understood, yet could contribute to the molecular diversity of cancer. Here, the authors analyze the diversity of genetic alterations, genes expressed and drug sensitivities among solid tumors to explore what evolutionary trade-offs may explain the molecular diversity of tumors.